El muro en el corazón de Palestina - Pappe, Ilan (Revista de Estudios Árabes, 2014)
The ill fated Oslo Accords and the construction of the Wall (most of it on Occupied Territories), end aspirations to create an independent Palestinian state. It is the final drive by Israel to block any geographic, political or cultural Palestinian identity. The first Intifada obliged Israel to accept the concept of some form of Palestinian entity. With the second, the Labor party invented the concept of separating both peoples, but keeping on their side of the Wall the majority of the settlements and Palestinian water resources, with Palestinian lands dissected into strictly isolated cantons, thus making possible continuous growth of the settlements. The result was the radicalization of both sides, making almost impossible to reach a permanent and mutually satisfactory agreement.